A Misdiagnosis of Traumatic Hypersupination of the Distal Radioulnar Joint: A Case Report - Vipin Asopa; Robert J. Douglas; Andrew D. Saies; James S. Church (Case Reports in Orthopedics)
Traumatic hypersupination injury of the distal radioulnar joint is a rare injury, and occurs when sufficient supination force is applied to the joint so as to tear the volar radioulnar ligament, resulting in separation of the triangular fibrocartilage complex, and subluxation of the tendon of extensor carpi ulnaris. This allows the distal ulna to rotate such that the ulnar styloid comes to lie adjacent to the ulna notch of the radius. Treatment of this injury requires manipulation of the joint, under anaesthesia or sedation. We describe a case where posttraumatic radiological investigation of a patient with an anatomical variation of the wrist when in supination resembled a traumatic hypersupination injury of the distal radioulnar joint. A review of the literature has revealed this to be the first reported case of this type.